Antioxidative and Anti-Inflammatory Effects of Lactobacillus plantarum ZS62 on Alcohol-Induced Subacute Hepatic Damage - Gan, Yi; Chen, Xiufeng; Yi, Ruokun; Zhao, Xin (Probiotics and Oxidative Stress, 2022)
Lactobacillus plantarum ZS62 is a newly isolated strain from naturally fermented yogurt that might offer some beneficial effects in the setting of alcohol-induced subacute liver injury. The liver-protective effect of L. plantarum ZS62 was investigated by gavage feeding of mice with this Lactobacillus strain (1x109 CFU/kg BW) before alcohol administration daily for 7 days. We then compared hepatic morphology, liver function indexes, liver lipid levels, inflammation, oxidative stress levels, and mRNA expression of oxidative metabolism- and inflammation-related genes in mice that had been pretreated with Lactobacillus plantarum versus control mice that had not been pretreated. Our results showed that L. plantarum ZS62 attenuated alcohol-induced weight loss; prevented morphological changes in hepatocytes; reduced markers of liver damage including aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), hyaluronidase (HAase), precollagen III (PC III), and inflammatory cytokines; and enhanced the antioxidative status. L. plantarum ZS62 also significantly downregulated inflammation-related genes and upregulated lipid- and oxidative-metabolism genes. Thus, Lactobacillus plantarum pretreatment appears to confer hepatic protection by reducing inflammation and enhancing antioxidative capacity. The protective effect of L. plantarum ZS62 was even better than that of a commonly used commercial lactic acid bacteria (Lactobacillus delbrueckii subsp. Bulgaricus). The L. plantarum ZS62 might be a potentially beneficial prophylactic treatment for people who frequently drink alcoholic beverages.